Assay of direct digital output floating-wiper resistive displacement sensor. (25th November 2020) - Mohan, Aparna; Mohanasankar, S; Jagadeesh Kumar, V
Abstract: The principle of operation of a successive approximation type direct displacement to digital converter for a floating-wiper resistive potentiometric sensor, presented earlier, is analyzed in detail to ascertain possible sources of error that can affect the performance of the transducer. Based on the analysis the method is suitably modified to improve its performance. To establish the efficacy of the altered scheme, a prototype signal conditioning circuit has been built and tested using both an emulated sensor and a prototype sensor. While the worst-case error in the former was found to be 0.5%, it was less than 0.8% in the latter. The test results indicate that the digital output is directly proportional to the per-unit displacement and is independent of the value of the coupling capacitance between the floating-wiper and the resistive element.